Pola Komunikasi Keluarga dan Kemampuan Sosialisasi Anak Prasekolah Di TK Kuncup Harapan Desa Bendungan Kecamatan Kudu Kabupaten Jombang - Noerma Kurnia fajarwati; Aditya Faziawan Azhar; Ahmad Adnil Hannaf; Firman Darussalam (Pusat Riset dan Inovasi Nasional, 2024)
The family communication patterns play a role in the socialization development of preschool children at TK Kuncup Harapan, Bendungan Village, Kudu District, Jombang Regency. This study aims to identify the dominant family communication patterns and evaluate their impact on the socialization abilities of preschool children at the mentioned kindergarten. The research method employed is literature review. The gathered data is qualitatively analyzed to uncover the dominant family communication patterns and their relation to the socialization abilities of preschool children. The research findings indicate that open and responsive family communication patterns tend to facilitate the socialization development of preschool children. Conversely, authoritarian or less open communication patterns may hinder the socialization abilities of children. In conclusion, family communication patterns play a key role in shaping the socialization abilities of preschool children.